BSCI-01. ACTIVATION OF c-Met/β1-INTEGRIN COMPLEX RESULTS IN INCREASE OF MESENCHYMAL GENE EXPRESSION AND STEM CELL POPULATION IN METASTATIC BREAST CANCER TO THE BRAIN AND SPINE. (12th August 2019) - Lau, Darryl; Wadhwa, Harsh; Nguyen, Alan; Chandra, Ankush; Aghi, Manish
Abstract: INTRODUCTION: C-met and β-integrins play a central role in nearly all stages of cancer metastasis. They bind at the cell surface, driving ligand independent co-activation of downstream pathways. Greater complex is seen in metastatic tumors vs. its primary tumor counterparts in patients. The molecular, cellular, and clinical effects of complex formation in metastatic breast cancer are investigated. METHODS: Utilizing variations of the MDA-231 breast cancer cell lines (standard MDA-231, inducible complex formation MDA-231, brain seeking MDA 231, lung seeking MDA 231, and bone seeking MDA-231), in vitro and in vivo studies were performed. Clinical correlates from patient samples were studied. RESULTS: Induction of c-Met/β1 complex promotes breast cancer invasion (p< 0.001), migration (p< 0.05), circulation intravasation (p< 0.01), and adhesion (p< 0.01). These effects may be driven by the increased mesenchymal character (p< 0.05) and larger stem cell population (p< 0.001) caused by inducing c-Met/β1 complex formation. OS2966 (a therapeutic β1 integrin blocking antibody) decreases invasion (p< 0.05), intravasation (p< 0.05), and mesenchymal form factor (p< 0.001) and gene expression (p< 0.001) in MDA-MB-231 cells. Brain- and bone-seeking breast cancer cells have higher c-Met/β1 complex than parental controls and preferentially adhere to tissue-specific matrix (p< 0.01). In intracardiac metastasis models, complex formation resulted in significantly higher metastatic burden and shorter survival times (p< 0.001). qPCR data suggests that complex formation may drive exiting and colonization of cancer cells (micrometastasis) rather than tumor growth. Patient brain and bone metastases demonstrated high β1/c-Met levels. CONCLUSIONS: The c-Met/β1 complex drives intravasation and extravasation of breast cancer cells from the circulation. Preferential affinity for tissue-specific matrix enables the c-Met/β1 complex to drive formation of breast cancer metastases to the brain and bone. Pharmacological and genetic targeting of the complex with agents may provide therapeutic approaches to prevent metastases, particularly to the brain and bone.